The /ka-/ and /kra-/ prefixes in Thai - Bilmes, Leela (2024)
It has been noted (Varasarin 1984; Siri-aksornsat 1996) that the Thai language has many words beginning with the prefixes /ka-/ and /kra-/. The same prefixes /ka- kra-/ exist in Khmer. Jenner (1982) shows that Khmer prefixes phonologically realized as /ka-/ or /kra-/ may in fact be one of three different prefixes: a velar prefix which indicates "generalized intensification"; a reduplicated initial consonant, also indicating intensification; and a velar prefix which designates nouns of five specific types (pp. xxxviii-xli). We find that the velar prefixes behave the same way in Thai as they do in Khmer, and Varasarin argues that not only are the prefixes borrowed, but that the whole process of derivation is borrowed from Khmer into Thai.